Self-organised urban space without profit : Four examples in Berlin - Schwarz, Stephan; Sabatier-Schwarz, Ingrid (AESOP, 2017)
The following article explores the interdependency between urban crisis as a pre-condition for self-organised responses to it and self-organised projects that try to provide solutions for problems caused by the respective crisis. Berlin is taken as specific field of investigation as self-organisation is very much linked to its recent history and it therefore seems to be a very relevant case for this topic. The example of the International Building Exhibition 1984/1987 in Berlin (IBA 84/87) is studied as a historic reference to provide a framework for comparing more recent processes with a long-term experience since the late 1980’. Four recent examples of self-organised projects that aim to provide spaces without profit are presented with the focus on their creation processes. The article further explores the specific relationship between Berlins’ actual housing crisis and various forms of self-organised reactions to it. Finally, the research tries to explore possible impacts these projects might have on formal local planning structures in a long-term perspective.
plaNext-Next Generation Planning Vol. 5 (2017): Spatial governance: Bridging theory and practice 78-90
Keywords: Berlin; production of space; self-organisation; real estate; housing